GENDER DIFFERENCES IN WRITING ANXIETY AMONG EFL UNDERGRADUATE STUDENTS: A SURVEY STUDY AT UNIVERSITAS JAMBI - Fajaryani, Nunung; Failasofah, Failasofah; Abrar, Mukhlash; Masbirorotni, Masbirorotni; Septi Handayani, Lucy (English Review: Journal of English Education, 2024)
Writing is a skill that is necessary for success in the academic world. Writing is a necessary activity in education that fosters significant growth in both teaching and learning. However, good writing requires a variety of skills, including a wide vocabulary, the capacity for contextual understanding, analytical strength, the capacity for inference, the capacity for critical thought, and much more. This skill is unquestionably difficult to acquire, especially when writing in English, which naturally puts more pressure and anxiety on students. This study was designed to investigate the types and levels of writing anxiety experienced by EFL students taking an academic writing course at an English department at a university in Jambi, regardless of their gender. The instrument of this study was a close-ended questionnaire that was adopted from Cheng (2004). It consists of 22 statements about different types of anxiety (cognitive, somatic, and avoidance behavior). There were 225 students who participated in the study. Majority of them 82.2% (185 students) were female and only 17.8% (40 students) were male. The results of the study indicated that there are differences in the level of anxiety experienced by male and female students. The highest score of the two genders is in the somatic anxiety type; namely, women have a mean score of 3.36 and men have a mean score of 3.07. Although both have high levels, there is a slight difference in numbers, so women experience higher levels of anxiety than men, and the type of anxiety they have is somatic anxiety.